The Escape Gap Effectiveness of Collapsible Trap to Catch Swimming Crab (Portunus pelagicus) in Banten Bay) - Anggi Kurniasih; Ririn Irnawati; Adi Susanto (Jurnal Perikanan dan Kelautan, 2016)
Swimming crab is one of an economic fisheries commodity in Banten Province. One of the fishing gear to catch swimming crabs is collapsible trap. The objective of this study is to analyze the effectiveness of escape gap on collapsible traps for catching swimming crab in Banten Bay. This research uses experimental fishing. The escape gap have 4 cm in length and 3 cm in width to release the swimming crabs with carapace width < 10 cm. This research was conducted in January-February 2015 in Banten Bay. The total 84 swimming crab consist of 40 males and 44 females. With total weight 15,556 g. The carapace width distribution in this study ranged from 6,5 to 14,1 cm. The application of escaping gap have high effectiveness to catch the legal size of swimming crab with proportion 84%.